Three new species of Kalcerrytus Galiano, 2000 from Brazil (Araneae: Salticidae) - Bustamante, Abel A.; Ruiz, Gustavo R.s. (Zootaxa, 2016)
Three new species of Kalcerrytus Galiano, 2000 from the state of Pará in the Brazilian Amazon are described: K. amplexus sp. nov. from Parque Nacional da Serra do Pardo, São Félix do Xingu, K. filipi sp. nov. from Reserva Ecológica do Jari, Almeirim, and K. leonardi sp. nov. from Juruti. These increase up to 18 the described species within the genus.